Factors Affecting the Success of Exclusive Breastfeeding - Melia Dwi Yitna Putri; Mufdlilah Mufdlilah; Herlin Fitriani Kurniawati (Syntax Idea)
This study aims to determine the factors that influence the success of exclusive breastfeeding. Some of the factors studied include maternal factors, infant factors, environmental factors, socioeconomic factors, and support factors. The data filtering process is using PRISMA Flowchart. PRISMA is a Preferred Reporting Items for Systematic review and Meta-Analyses, developed to assist authors in reporting Systematic Reviews and Meta-Analyses. The results of this study show that the factors that influence the success of exclusive breastfeeding. Maternal Factors: Knowledge of breast milk, positive attitude towards breast milk, mental and physical readiness for breastfeeding, and support from family and environment. Support Factor: Support from husband, family, and community in providing exclusive breastfeeding. In conclusion, it was found that the factors that affect the success of exclusive breastfeeding in young mothers are influenced by several factors including maternal age, maternal milk production, support of the closest person, experience of breastfeeding mothers, and parity. Support is needed to provide counseling, knowledge about the importance of exclusive breastfeeding to their babies, and motivation to mothers and breast care.